Impact of pandemic COVID-19 on dermatology and venereology outpatient clinic in a tertiary referral hospital in Yogyakarta, Indonesia - Alessandro Alfieri; Flandiana Yogianti (PAGEPress Publications, 2021)
COVID-19 has spread throughout the world rapidly, including in Indonesia. During this pandemic, there are differences in the number and types of patient cases who attend the dermatology and venereology outpatient clinic. This study aimed to investigate the differences in the number of cases, disease profiles, diagnostic procedures and therapy procedures before and during the COVID-19 pandemic in the dermatology and venereology outpatient clinic in Dr. Sardjito General Hospital, Yogyakarta, Indonesia. At the beginning of the COVID-19 pandemic, there was a 61.2% decrease in patients visiting outpatient clinic compared to the same period in previous year. There was also a decrease in the number of diagnostic procedures and therapeutic procedures performed in the outpatient clinic. For the disease profile of the total number of patients who visited the outpatient clinic, there was a slight difference. In 2019, the number of cases of acne vulgaris became the second largest, but in 2020, the number of cases of acne vulgaris decreased to the fifth largest. These results support the finding that COVID-19, although not a skin disease, has an impact on dermatology and venereology outpatient clinic.